Sleep Duration in Adolescence and Its Prenatal, Perinatal, and Health Determinants in a Large Population-based Cohort Followed from Birth - Barbara Berrutti; Mariana Otero Xavier; Iná S. Santos; Alicia Matijasevich; Luciana Tovo-Rodrigues (Sleep Science, 2023)
Objective To investigate sleep duration and its associated factors in adolescents aged 11 years from the 2004 Pelotas (Brazil) Birth Cohort Study.